Trasformare le norme. Il case-study del sex trafficking minorile in Thailandia (Società e diritti, 2022)
This article investigates the main issues characterizing the legal approach to child sex trafficking in Thailand. Thearticle discusses the possibility to adopt an alternative sociological approach aimed to change Thai social norms.The first part of the article (§§ 1-2) describes the peculiarity of sex trafficking in Thailand and offers an overview ofthe current policies in sex trafficking control, showing their limits and strengths. The second part of the article (§§3-4) discusses the features of Cristina Bicchieri’s theory of social norms (identifying non-social and social beliefsas primary catalysts of social change) and reflects on its application to the Thailand social and cultural settings.